Gambaran Tingkat Pengetahuan Ibu Nifas tentang Inisiasi Menyusui Dini (IMD) - Dwi Prima Hanis Kusumaningtiyas; Roslina Mone (Indonesian Journal of Health Research, 2018)
Introduction. Early Breastfeeding Initiation is breastfeeding newborns, immediately embracing and letting the baby suckle in the first hour of birth, without being cleaned and not separated from the mother. Helps reduce poverty, help reduce hunger because breastfeeding can the role of MDGs (Millennium Development Goals) in achieving Early Breastfeeding Initiation is to increase the success of exclusive breastfeeding and the length of breastfeeding, meet the baby's food needs until the age of two years, helping to reduce child and under-five mortality. The provision of ASI is known as one of the things that has the most influence on the survival, growth and development of children. Methods. The research design used was descriptive with a cross-setional approach, probability sampling technique, namely simple random sampling with a sample of 47 people. Statistical analysis that is used in descriptive is a way of analysis by systematically composing in the form of sentences or categories regarding the subject so that finally a general conclusion is obtained. Results. The results showed that respondents aged 20-35 years (85.11%), with high school education level (38.30%), some primiparous parity respondents (55.32%), never received information (36.17%) and have a lack of knowledge (48.94%). Conclusion. The researchers concluded that most of the respondents were less knowledgeable about Early Breastfeeding Initiation and for health workers to provide counseling, information and education to mothers during pregnancy visits related to Early Breastfeeding Initiation.